Effectiveness of Infusion Warmer Use to Prevent the Occurrence of Hypothermia and Shivering After General Anesthesia Action in General Hospital Center Sanglah Denpasar - Wiryana, Made; Sinardja, I Ketut; Budiarta, I Gede; Agung Senapathi, Tjokorda Gde; Widnyana, Made; Aryabiantara, I Wayan; Utara Hartawan, I Gusti Agung Gede; Parami, Pontisomaya; Kusuma Wijaya, Andi; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Introduction: Shivering and hypothermia after general anesthesia is a common complication in the recovery room. Heating methods and drugs Â widely used, but not yet effective. The purpose of this study was to evaluate the effectiveness of using the infusion warmer in maintaining normal core temperature and prevent shivering. Materials and Methods: The study was a non blindnes randomized control trial study. This study aimed to compare the effectiveness of the use of infusion warmer in preventing the incidence of hypothermia and shivering after general anesthesia. Research conducted at the Sanglah Hospital in October 2016, with sample calculations 58 people who meet the inclusion and exclusion criteria. Both were divided into 2 groups, 29 groups of infusion warmer and 29 people without the infusion warmer Recording the results of assessing multiple parameters vital signs, hemodynamic, aldrette score, body temperature, and shivering from the beginning, after induction, and minutes to 5, 15, 30 , 60 in the recovery room. The data obtained were analyzed with SPSS software with a significance level of p <0.005 expressed significantly, with a relative risk <1 as a preventive. Results: From a comparative picture of events shivering and hypothermia in minutes to 5, 15, 30, 60 in the recovery room seen that the treatment group based on the group lower warmer than in the non warmer. This shows that the use of warmer can prevent the incidence of shivering and hypothermia in patients after general anesthesia. In test statistically significant with p <0.05. Conclusions: The use of infusion warmer can help reduce the incidence of hypothermia and shivering after general anesthesia action.